Impact of the COVID-19 pandemic on physical, psychological and utritional characteristics of elite athletes: A cross-sectional web survey - Esht, V.; Jain, Y.; Chikara, R.; Sharma, S. (Bioscience Biotechnology Research Communications, 2021)
COVID-19 has upended sports and sporting calendars worldwide; causing postponement or cancellations of sports events globally. Amid the lockdown, most of the athletes are left on their own at their homes. This study investigates the impact of the ongoing Pandemic on physical, psychological and nutritional characteristics of elite athletes amid COVID-19 spread. A cross sectional web survey was carried out using a validated questionnaire comprising of total 19 questions regarding the demographic details, physical, psychological and nutritional characteristics of elite athletes before and after COVID-19 Spread. The normality of data was established using Kolmogorov-Smirnov test. The frequency and percentage n (%) of ordinal data of participant responses were calculated. A total of ninety four elite athletes voluntarily participated, out of which 73 (78%) were male athletes.